Audit of cancer pain management practices at the adult oncology center, University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia - Asmare, Temesgen Birlie; Tawuye, Hailu Yimer; Tegegne, Biresaw Ayen; Gobezie, Negesse Zurabachew; Wubet, Habtie Bantider; Gedefaw, Gezahagn Demisu; Tadesse, Molla Amsalu; Admass, Biruk Adie (Frontiers in Oncology, 2025)
IntroductionCancer is one of the leading causes of death globally, with an estimated 19.3 million new cancer cases and nearly 10.0 million cancer deaths occurring in 2020. Pain is common among patients with cancer, particularly in the advanced stages of the disease, where the prevalence is estimated to exceed 70%. In our setting, the prevalence of cancer pain is high (59.9%), which makes the study of cancer pain management essential in order to identify specific gaps in current practices. This research aimed to enhance the quality of pain management and to improve patient care and safety in accordance with the European Society of Medical Oncology (ESMO) cancer pain management guidelines.MethodA hospital-based cross-sectional study was conducted from July 2 to August 1, 2024. All consecutive adult patients in the oncology ward during this period were included. Data were collected according to the ESMO guidelines through direct observations, chart reviews, and interviews. The data were then entered into EpiData version 4.6 and exported to Stata version 17 for analysis.ResultThe study included 171 patients, of whom 96 (56.14%) were women. The overall compliance rate for oncologic pain management according with the ESMO guidelines was 55.46%. The ages of the participants ranged from 23 to 85 years, with a mean age of 51.2 years. The pain severity and the treatment outcomes were assessed regularly and consistently using the Numeric Rating Scale (NRS) for all 171 patients (100%). However, the subcutaneous route was considered as the first choice in only 2 (1.16%) patients who were unable to receive opioids via the oral route.Conclusion and recommendationsIn this study, the overall compliance with the adult oncologic pain management guidelines was found to be suboptimal. It is recommended to establish a regular training program for healthcare professionals focusing on oncologic pain management.